Reaching for the ‘first 95’: a cross-country analysis of HIV self-testing in nine countries in sub-Saharan Africa - Empel, Eva van; De Vlieg, Rebecca A.; Harling, Guy; Marcus, Maja E.; Kahn, Kathleen; Bärnighausen, Till; Montana, Livia; Choko, Augustine T.; Manne-Goehler, Jennifer (AIDS <London>, 2022)
Objectives: - HIV self-testing (HIVST) offers a promising approach to increase HIV diagnosis and advance progress towards the UNAIDS 95-95-95 targets. We aimed to understand patterns of HIVST awareness and utilization in nine sub-Saharan African (SSA) countries, with the goal of identifying populations to target in disseminating this technology. - Design: - A cross-sectional study. - Methods: - We pooled individual-level population-based data from nine Demographic and Health Surveys (DHS) in SSA conducted 2015-2019 (Burundi, Cameroon, Guinea, Malawi, Senegal, Sierra Leone, South Africa, Zambia, Zimbabwe). Primary outcomes were HIVST awareness and utilization. We used logistic regression with survey fixed effects to explore the relationship between sociodemographic characteristics and these outcomes. Models were adjusted for sex, age, rural/urban residence, education, wealth, and marital status. We accounted for complex survey design. - Results: - The study sample included 177 572 people (66.0% women, mean age 29 ± 10 years), of whom 86.6% [95% confidence interval (95% CI) 86.4-86.7] were unaware of HIVST, 11.7% (95% CI 11.6-11.9) were aware of but never used HIVST, and 1.7% (95% CI 1.6-1.8) had used HIVST. In adjusted models, women were less likely to be aware of HIVST [odds ratio (OR) 0.75, 95% CI 0.71-0.79], but more likely to have used HIVST (OR 1.17, 95% CI 1.03-1.32) compared with men. Rural residents, those who were least educated, and poorest were less likely to have heard of or used HIVST. - Conclusion: - HIVST awareness and uptake were low. Rural, less educated, and lower income populations were least likely to have heard of or used HIVST. Efforts to scale-up HIVST in these settings should aim to reach these less advantaged groups.